Analisis Kualitas Butir Soal Buatan Guru Kimia Pada Tes Ujian Tengah Semester Ganjil Kelas XII MIPA - Hendrik Simamora; Hartono Hartono; Effendi Effendi (Universitas Pendidikan Mandalika Mataram, 2021)
This researchi is want to knowithe test quality of items in the mid semester for XII Grade of SMA Negeri 1 PematangsiantarIin academic yearI 2020/2021 basic on terms of reliability test, validity, difficulty index, descriminationi index and disctractor. The research have used thecollecting data’s method was documentation and to collect some of test item, student answer sheet, answer key and so do interview to chemistry teachers in this school. Research used subject in this school were grade XII Science 1,2,and 3 of the science students of SMA Negeri 1 Pematangsiantar with total of subject 108 students based on purposive sanpling that researcher which has been used. The research have used method ofIanalyzed was quantitative descriptiveIconducted and it has used softwere program based of SPSSIversion 25 and Anates version 4.0.9. The result of the research concluded that the quality of the test item has some of category such as showed 2 items (10%) had very good quality and 2 items (10%)too had poorIquality of test and extremely poor quality in same test and should be suggest to thrown awayand 8 items (40%) known that has good quality, 4 (20%) has moderately quality, 3 (15%) has poor quality of item test and conclude that the quality of item test had moderately good quality based on this research.